Conservative Management of the Duodenal Injury during Percutaneous Nephrostomy Placement: A Few and Far between Complications of the Urological Literature. (31st December 2021) - Colakerol, Aykut; Temiz, Mustafa Zafer; Adem, Mubarek Bargicho; Ozdogan, Kamil; Celebi, Fatih; Kandirali, Engin; Muslumanoglu, Ahmet Yaser
Abstract : Herein, we reported a duodenal perforation case as an intestinal injury during a percutaneous nephrostomy procedure. A 73-year-old woman with bilateral nephrostomy catheters was applied to the emergency service with right flank pain. Early in the day, her bilateral nephrostomy catheters had been changed. On physical examination, she had a defense and rebound at her right quadrant, and costovertebral angle tenderness was also positive. In the contrast-enhanced abdominal computed tomography scan, the right nephrostomy catheter was located in the second part of the duodenum, and the contrast agent did not leak into the peritoneum from the injury area. We decided on conservative management of the case with active surveillance using daily blood tests and physical examinations. The nephrostomy catheter in the duodenum was left to prevent fistula between the duodenum and the skin, and a new one was placed in the right kidney. The broad spectrum antibiotherapy regime was applied, and the patient was followed up closely. The catheter in the duodenum was removed on the 20th day, uneventfully, and the patient was discharged successfully on the 24th day with her permanent bilateral nephrostomy tubes. On the first follow-up, one month later, the patient had no active medical complaint.